2006
DOI: 10.1007/s11524-005-9006-5
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and HIV/AIDS in the New York Metropolitan Area

Abstract: Because the HIV pandemic undergoes continual change in its locations and affected populations, it is crucial to study HIV risk behaviors among mobile and immigrant groups within and across borders. The impact of cross-cultural migrations and the importance of studying that impact in terms of demographic characteristics as well as cultural and environmental factors has not received adequate attention in public health research. This collaborative analysis utilizes data from three studies of immigrant groups in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…Similar to trends seen in other developed countries [22][23][24][25][26][27][28][29], our immigrant/refugee population, especially those from Sub-Saharan Africa, is diagnosed at a later stage in their HIV infection, with lower CD4 counts, a larger percentage of females, different HIV subtypes, and a different array of co-morbidities previously rare for Canada, such as tuberculosis and toxoplasmosis. We found that management and monitoring of disease progression is more intense, requiring more clinic al visits and laboratory testing to anticipate the different responses to treatment by the various non-B subtypes as discussed in Spira et al [18].…”
Section: Discussionsupporting
confidence: 77%
“…Similar to trends seen in other developed countries [22][23][24][25][26][27][28][29], our immigrant/refugee population, especially those from Sub-Saharan Africa, is diagnosed at a later stage in their HIV infection, with lower CD4 counts, a larger percentage of females, different HIV subtypes, and a different array of co-morbidities previously rare for Canada, such as tuberculosis and toxoplasmosis. We found that management and monitoring of disease progression is more intense, requiring more clinic al visits and laboratory testing to anticipate the different responses to treatment by the various non-B subtypes as discussed in Spira et al [18].…”
Section: Discussionsupporting
confidence: 77%
“…The future of HIV/ AIDS in the Dominican Republic is particularly tenuous because of a multitude of factors that connect the epidemic to communities outside the country. There is a porous border the country shares with Haiti where the adult prevalence is the highest in the Western hemisphere, a large flux of immigrants to and from the United States and Caribbean neighbours, and the Dominican Republic remains a popular destination for sex tourism (Brewer et al, 1998;Forsythe et al, 1998;Shedlin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To control the epidemic, it is imperative that interventions focus on safe sex practices in high-risk groups, yet little is known about sexual risk behaviours among HIV-positive patients in the Dominican Republic. There is little adult clinical behavioural research from this nation and previous studies have focused on sexual risk factors in specific sub-populations Á commercial sex workers and those who live in the bateys, sugar cane plantations home to high numbers of migrant Dominican and Haitian labourers (Brewer et al, 1998;Forsythe et al, 1998;Shedlin et al, 2006;Cohen, 2006;Kerrigan et al, 2006). Secondary prevention efforts, however, must be targeted at infected individuals across a range of communities.…”
Section: Introductionmentioning
confidence: 99%
“…The future of HIV/AIDS in the Dominican Republic is particularly tenuous because of a multitude of factors that connect the epidemic to communities outside the country. There is a porous border the country shares with Haiti where the adult prevalence is the highest in the Western hemisphere, a large flux of immigrants to and from the United States and Caribbean neighbors, and the Dominican Republic remains a popular destination for sex tourism (Brewer et al, 1998;Forsythe, Hasbun, & Butler de Lister, 1998;Shedlin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To control the epidemic, it is imperative that interventions focus on safe sex practices in high-risk groups, yet little is known about sexual risk behaviors among HIV-positive patients in the Dominican Republic. There is little adult clinical behavioral research from this nation and previous studies have focused on sexual risk factors in specific sub-populations Á commercial sex workers and those who live in the bateys, sugar cane plantations home to high numbers of migrant Dominican and Haitian laborers (Brewer et al, 1998;Cohen, 2006;Forsythe et al, 1998;Kerrigan et al, 2006;Shedlin et al, 2006). Secondary prevention efforts, however, must be targeted to infected individuals across a range of communities.…”
Section: Introductionmentioning
confidence: 99%